KOSMOLOGI HARUN YAHYA DAN KRITIKNYA TERHADAP MATERIALISME: INTEGRASI AGAMA DAN SAINS - Juwaini, Juwaini; Rahmasari, Lilis Suci (Prodi Studi Agama-Agama, 2022)
This study aims to discuss the concept of cosmology Harun Yahya in the Koran with the theory (Big Bang) and his criticism of the concept of materialist cosmology. This paper uses library research and analysis of the character's thoughts, starting with examining all available data from primary sources, namely Harun Yahya's book, entitled